Evaluation of Response Criteria in Rheumatoid Arthritis Treated With Biologic Disease‐Modifying Antirheumatic Drugs. Issue 7 (5th June 2020) - Inoue, Mariko; Kanda, Hiroko; Tateishi, Shoko; Fujio, Keishi
Abstract : Objective: Biologic disease‐modifying antirheumatic drugs (bDMARDs) used for rheumatoid arthritis (RA) treatment have several mechanisms of action. Interleukin‐6 inhibitors (IL‐6i) block the production of acute‐phase reactants (APRs), which are some of the composite measures of disease activity. We undertook this study to examine the agreement between the European League Against Rheumatism (EULAR) response based on the erythrocyte sedimentation rate (ESR) or C‐reactive protein level, the Simplified Disease Activity Index 50% response measure (SDAI50), and the Clinical Disease Activity Index 50% response measure (CDAI50) in patients treated with IL‐6i and other bDMARDs. Methods: We enrolled 306 patients with RA who started or switched bDMARDs. Treatment response at 6 months was analyzed. Kappa statistics were used to evaluate the agreement between different response measures. The contribution of APRs to improvement in disease activity scores was examined. The change of Health Assessment Questionnaire (HAQ) score was analyzed in IL‐6i–treated patients. Results: Good agreement was achieved between response measures, with κ >0.6 in patients treated with tumor necrosis factor inhibitors or cytotoxic T‐lymphocyte–associated antigen 4 immunoglobulin fusion protein. In IL‐6i–treated patients, the agreement was low between the EULAR response (ESR) and the SDAI50 or the CDAI50 (κ = 0.43 and 0.37, respectively). Under IL‐6i treatment, APR improvement accounted for 56.0% of total improvement of the Disease Activity Score in 28 joints (DAS28) using the ESR. When discordance was found between the CDAI50 and EULAR response in IL‐6i–treated patients, all patients were classified as EULAR‐only responders; there was no HAQ improvement in EULAR‐only responders. Conclusion: EULAR response criteria overestimate the response under IL‐6i treatment because the APR improvement largely contributes to the DAS28 improvement.